2008
DOI: 10.1002/mrc.2352
|View full text |Cite
|
Sign up to set email alerts
|

1H and 13C NMR assignments of new methoxylated furanoflavonoids from Lonchocarpus araripensis

Abstract: Two new polymethoxylated flavonoids, 2',5',6'-trimethoxy-[2'',3'' : 3',4']furano dihydrochalcone and 2,4',4,5-tetramethoxy-[2'',3'' : 6,7]-furanodihydroaurone, were isolated from the root barks of Lonchocarpus araripensis, along with the known compounds 3,4,5,6-tetramethoxy-[2'',3'' : 7,8]-furanoflavan, 3,6-dimethoxy-1'',1''-dimethylcromene-[2'',3'' : 7,8]-flavone, 3',4'-methylenodioxy-5,6-dimethoxy-[2'',3'' : 7,8]-furanoflavone, 3,5,6-trimethoxy-[2'',3'' : 7,8]-furanoflavanone, 3,5,6-trimethoxy-[2'',3'' : 7,8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…415 The furano-functionalised auronol 552 is one of two highly O-methylated flavonoids (see also 519) isolated from root bark extracts of Lonchocarpus araripensis (Leguminosae). 400 Complete assignment of the 1 H and 13 C NMR spectra of 552 using two-dimensional methods points to some inconsistencies in earlier sets of NMR data published for auronols, including that of 4 0 -chloroauronol, for which a chemical shift value of 169.0 ppm quoted for the carbonyl carbon is atypical. 400 This chlorinated auronol was obtained from a large-scale extraction of the marine brown alga Spatoglossom variabile together with (Z)-4 0 -chloroaurone.…”
Section: Auronesmentioning
confidence: 96%
“…415 The furano-functionalised auronol 552 is one of two highly O-methylated flavonoids (see also 519) isolated from root bark extracts of Lonchocarpus araripensis (Leguminosae). 400 Complete assignment of the 1 H and 13 C NMR spectra of 552 using two-dimensional methods points to some inconsistencies in earlier sets of NMR data published for auronols, including that of 4 0 -chloroauronol, for which a chemical shift value of 169.0 ppm quoted for the carbonyl carbon is atypical. 400 This chlorinated auronol was obtained from a large-scale extraction of the marine brown alga Spatoglossom variabile together with (Z)-4 0 -chloroaurone.…”
Section: Auronesmentioning
confidence: 96%
“…Bibliographical research on chemical constituents already isolated from species of the genus Dahlstedtia, showed that flavonoids are among the compounds found in greater profusion, especially chalcones, flavones and flavanones (Magalhães, Tozzi, Magalhães, Blanco, & Soriano, 2004;Lima, 2007;Lima et al, 2009), and these compounds are characterized by the presence of prenylated groups, which are indicators of the evolution of these species (Garcez, Scramin, Nascimento, & Mors, 1988). According to Simões et al (2010), flavonoids represent one of the most important and diverse groups among the secondary metabolites present in plants, since it plays a fundamental role in the protection of the plant in response to microbial attack and against ultraviolet irradiation, protecting the underlying photosynthetic tissues from damage (Harborne & Williams, 2000;Lattanzio, Kroon, Quideau, & Treutter, 2008;Ignat, Volf, & Popa, 2011).…”
Section: Phytochemical Analysismentioning
confidence: 99%
“…In Brazil, Lonchocarpus araripensis Benth is largely distributed in the northeast region, where it is popularly known as ‘sucupira’. Different studies have shown that some species of Lonchocarpus exert antiinflammatory (Alencar et al ., ; Napimoga et al ., ) and gastroprotective (Reyes‐Chilpa et al ., ) activities and many flavonoids have been isolated (Lima et al ., ; Lima et al ., ), especially flavones (Lima et al ., ).…”
Section: Introductionmentioning
confidence: 99%